2005
DOI: 10.1080/09595230500286039
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of heroin users entering treatment: findings from the Australian Treatment Outcome Study (ATOS)

Abstract: The current study aimed to describe the characteristics (demographics, drug use, mental and physical health) of entrants to treatment for heroin dependence in three treatment modalities; and to compare these characteristics with heroin users not in or seeking treatment. Participants were 825 current heroin users recruited from Sydney, Adelaide and Melbourne: 277 entering methadone/buprenorphine maintenance treatment (MT), 288 entering detoxification (DTX), 180 entering drug-free residential rehabilitation (RR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
206
5
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(226 citation statements)
references
References 37 publications
(33 reference statements)
13
206
5
2
Order By: Relevance
“…In 2013, 17.50% of PWID had committed a property offence in the month preceding interview (compared to 19.36% in 2000) and 3.40% had committed a violent offence (compared to 7.73% in 2000) (Topp et al, 2001). When compared to other drug using populations, property crime amongst PWID appears to be relatively low, with previous studies reporting past month prevalence rates of 38-39% Patterson et al, 2000;Ross et al, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…In 2013, 17.50% of PWID had committed a property offence in the month preceding interview (compared to 19.36% in 2000) and 3.40% had committed a violent offence (compared to 7.73% in 2000) (Topp et al, 2001). When compared to other drug using populations, property crime amongst PWID appears to be relatively low, with previous studies reporting past month prevalence rates of 38-39% Patterson et al, 2000;Ross et al, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…Eligibility criteria for index participants included: (1) female gender, (2) age between 18 and 55 years, (3) did not report injecting drugs in the past 6 months, (4) reported sex with at least one male partner in the past 6 months, and (5) reported at least one of the following risk behaviors in the past 6 months: (a) more than two sex partners, (b) recent sexually transmitted infection (STI) diagnosis, and (c) having a high-risk sex partner (i.e., injected heroin or cocaine, smoked crack, HIV seropositive, or male who has sex with men). Index participants also referred their peer and risk network members to the study.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Studies of opiate and cocaine users in treatment have revealed high levels of depressive symptomology and dual diagnosis of drug use and depression are common. [3][4][5] Moreover, cessation of drug use is linked to a reduction in depressive symptoms. In a longitudinal study of recovery from heroin dependence, Hser 6 found that lower levels of psychological distress predicted long-term recovery, and individuals who reported recovery of five or more years had significantly lower levels of depressive symptomology as assessed by the Center for Epidemiological Studies Depression Scale (CES-D).…”
Section: Introductionmentioning
confidence: 99%
“…Mean SF-12 baseline health scores were higher than those obtained in ATOS [34] at intake (47.5 vs 43.7 for physical health and 35.4 vs 31.3 for mental health). Psychological problems in the sample are indicated by over one in three having a previous referral for mental health treatment.…”
Section: Discussionmentioning
confidence: 56%